Rodzina tatarska w Drugiej Rzeczypospolitej wobec transmisji kulturowej - Wróblewska, Urszula (Karkonoska Państwowa Szkoła Wyższa, 2011)
The subject matter of my article is analysis religion educational and cultural processes, which influenced in family on Polish Muslim Tatars during the period between World Wars. Chronological range overlaps 1918-1939 years. During that period, Poland built its State structures after a long time of partitions. I would like to display a multi-dimensional characteristic of Polish Tatars religion education. In my article I would like to answer to the question: What was important in transfer between generation in family of Tatars? I would also like to fili in ‘blank’ in the researches in the field of Tatars minority and family educational processes in the years 1918-1939.
Keywords: intergeneration; cultural heritage; Tatars; Muslims; Second Polish Republic